Anti-Seizure Prophylaxis in Critically Ill Patients with Traumatic Brain Injury in an Intensive Care Unit. Issue 5 (September 2015) - Sundararajan, K.; Milne, D.; Edwards, S.; Chapman, M. J.; Shakib, S.
The objectives of this prospective observational study were to determine the proportion of patients with traumatic brain injury who received effective anti-seizure prophylaxis. The study was conducted in a tertiary level ICU of a major trauma referral centre between February 2012 and August 2013. A total of 2361 patients were admitted to the ICU in this study period, of whom 125 patients (index) with traumatic head injury were included in this study. The patients had a mean age of 45 years (SD=19), a mean score on the Glasgow Coma Scale of 9 (SD=4), a mean injury severity score of 27 (SD=13) and a mean APACHE III score of 55 (SD=27). Only 13.6 % (17 of 125) of patients were given anti-seizure prophylaxis and phenytoin levels were measured in 9.6% (12 of 125). Although all 12 patients achieved an effective concentration for phenytoin therapy (>40 μmol/l) after the loading dose, no patient had their target concentration consistently maintained in the recommended therapeutic range (40 to 80 μmol/l) throughout the seven-day monitoring period. There was wide fluctuation in phenytoin levels in the patients in this study. Twenty-two (18%) of the index patients had post-traumatic seizures, indicating a high prevalence for this study. Poor compliance with guidelines could possibly explain this phenomenon. Future studies are needed to look at the dosing and monitoring of phenytoin and/or alternative anti-seizure prophylaxis in patients with traumatic brain injury.